Rationally designed CuFe2O4-mesoporous Al2O3 composite towards stable performance of high temperature water-gas shift reaction - Subramanian, Vijayanand; Gnanakumar, Edwin S.; Jeong, Dae-Woon; Han, Won-Bi; Gopinath, Chinnakonda S.; Roh, Hyun-Seog (Chemical Communications, 2013)
High temperature water-gas shift reaction was demonstrated for the first time on a CuFe2O4-mesoporous alumina nanocomposite between 350 and 550 degrees C with 70-80% CO-conversion using simulated waste derived syngas under realistic conditions. Despite high Al-content, the catalyst exhibited stable activity, which was attributed to the nano-architectured robust porous nature of alumina integrated with surrounding CuFe2O4.

Role of nanointerfaces in Cu- and Cu plus Au-based near-ambient-temperature CO oxidation catalysts - Gnanakumar, Edwin S.; Naik, Jarpla Madhusudhan; Manikandan, Marimuthu; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (ChemCatChem, 2014)
Disordered mesoporous Cu-doped ceria-zirconia (Cu0.1Ce0.85Zr0.05O2), and gold deposited (Au/Cu0.1Ce0.85Zr0.05O2) catalysts were synthesized and evaluated for CO oxidation. Onset of CO oxidation activity, and 50% (100%) CO2 formation occurs at room temperature (RT), and 77 (120)degrees C, respectively, with Cu0.1Ce0.85Zr0.05O2. A small amount of gold on Cu0.1Ce0.85Zr0.05O2 induces the sustainable oxidation catalysis around RT. Onset of copper reduction temperature decreases from 110 degrees C on Cu0.1Ce0.85Zr0.05O2 to 48 degrees C with Au/Cu0.1Ce0.85Zr0.05O2, highlighting the direct interaction between Cu and Au through a Cu-Au interface. Au particles with a (00 1) facet deposit on an oxygen-deficient site of (111) facet of CeO2-ZrO2. Any decrease in surface Cu-content with increasing Au-content further supports the Au-Cu-Ce/Zr interface interactions. Nanointerfaces of Au clusters on Cu next to oxygen-deficient sites of CeO2-ZrO2 facilitate all the elementary steps of the CO + O-2 reaction to occur in close proximity at ambient conditions.
Keywords: carbon monoxide; Gold; heterogeneous catalysis; Oxidation; redox